Analyzing a Net Zero Energy Building (NZEB) in the Climate Zone of Australia - Patel, Jay (Open Science Journal, 2021)
Buildings and Residential sectors are amongst the major energy consumers of Australia. But the maximum portion of the energy consumed by these buildings is lost due to construction, design, or use of appliances. A significant amount of energy can be saved through this sector, which will not only reduce energy demand, it would further remove a major load from the National Grid. This study assessed a building in the residential sector of Australia and proposed how the use of Passive, Active techniques and adoption of the NZEB concept can help save energy consumption of residential houses. Different techniques and their implementation in the building were performed through both qualitative and quantitative analysis. The results obtained from the study show the house load of the designed building, a solar system that can take up the entire load, its financial assessment, and how the use of energy-efficient appliances and the use of passive techniques can result in improvement of energy efficiency.